2007
DOI: 10.1037/1076-898x.13.4.224
|View full text |Cite
|
Sign up to set email alerts
|

The Model Human Processor and the older adult: Parameter estimation and validation within a mobile phone task.

Abstract: The authors estimate weighted mean values for nine information processing parameters for older adults using the Card, Moran, and Newell (1983) Model Human Processor model. The authors validate a subset of these parameters by modeling two mobile phone tasks using two different phones and comparing model predictions to a sample of younger (N = 20; M age = 20) and older (N = 20; M age = 69) adults. Older adult models fit keystroke-level performance at the aggregate grain of analysis extremely well (R = 0.99) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 150 publications
3
44
1
Order By: Relevance
“…Finally, the Model Human Processor (MHP), proposed by [55], is based on the same 624 division of the mind as perceptual, cognitive and motor subsystems (or processors), older adults see [56]. Again, most of the range of estimated time for cognition and action 631 selection is inconsistent with our results, which ideally require at least 140 ms for the 632 stimulus to be projected to the BG and 60 additional milliseconds for action selection.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Finally, the Model Human Processor (MHP), proposed by [55], is based on the same 624 division of the mind as perceptual, cognitive and motor subsystems (or processors), older adults see [56]. Again, most of the range of estimated time for cognition and action 631 selection is inconsistent with our results, which ideally require at least 140 ms for the 632 stimulus to be projected to the BG and 60 additional milliseconds for action selection.…”
contrasting
confidence: 56%
“…46 We found that the frequency and phase difference between oscillatory cortical areas, 47 the level of dopamine in the system and the examined time scale, all have a very sequentially perform selection tasks, the strongly-active cortical areas instruct the mode 53 of this selection via their oscillatory activity. Some frequency ranges promote the 54 exploitation of actions of which the outcome is known, others promote the exploration 55 of new actions with high uncertainty, while others simply deactivate the selection 56 mechanism. Finally, we identified a selection cycle with a period of around 200 ms, 57 which was used to assess the biological plausibility of the most popular architectures in 58 cognitive science.…”
mentioning
confidence: 99%
“…Second, the ACT asked participants to enter the moves on a computer within 30 s, and it was apparent that failure to do this was correlated fairly significantly with age, r(226) = .468, p < .001. A cardinal feature of adult aging is that the rate of information processing for many tasks is slowed (Jastrzembski & Charness, 2007;Salthouse, 1996), and this has been shown even for skilled chess players doing chessrelated processing (Jastrzembski, Charness, & Vasyukova, 2006). This slowing seemed partly responsible for the fact the the ACT is a fairly strong outlier in the best move data.…”
Section: Methodsmentioning
confidence: 99%
“…Ziefle and Bay [13] conducted comparative evaluation of two mobile phones of different complexity between younger and older participant groups. Jastrzembski and Charness [8] proposed and validated the parameters of a Model Human Processor for older adults.…”
Section: Elderly Users and Mobile Phonesmentioning
confidence: 99%
“…On the other hand, there have also been works that sought to capture more concretely the patterns and tendencies of elderly users' interaction with mobile touchscreen devices through measurement and analysis of low-level interaction metrics such as task speed and accuracy [8][9][10][11][12][13]. Most of these works involved experiments in which the participants performed primitive actions such as tap or swipe gestures in isolation within their custom test applications.…”
Section: Introductionmentioning
confidence: 99%